2016
DOI: 10.1186/s13008-016-0025-2
|View full text |Cite
|
Sign up to set email alerts
|

The CSL proteins, versatile transcription factors and context dependent corepressors of the notch signaling pathway

Abstract: The Notch signaling pathway is a reiteratively used cell to cell communication pathway that triggers pleiotropic effects. The correct regulation of the pathway permits the efficient regulation of genes involved in cell fate decision throughout development. This activity relies notably on the CSL proteins, (an acronym for CBF-1/RBPJ-κ in Homo sapiens/Mus musculus respectively, Suppressor of Hairless in Drosophila melanogaster, Lag-1 in Caenorhabditis elegans) which is the unique transcription factor and DNA bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 99 publications
(208 reference statements)
0
22
0
Order By: Relevance
“…Multiple mammalian “co-repressor” genes encode proteins that interact with Rbpj via CSL binding sites 56 . These genes are unrelated at the primary sequence level, but predicted to link Rbpj to HDAC machinery, and include Smrt/Ncor2 , Spen/Mint/Sharp , Fhl1b//KyoT2 , Rita , Skip , L3mbtl3 and Kdm1a/Lsd1 57 59 . Interestingly, Kdm1a/Lsd1 is expressed in the retina from E17-P15, and its pharmacologic inhibition in retinal explants induced an upregulation of bHLH factor expression 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple mammalian “co-repressor” genes encode proteins that interact with Rbpj via CSL binding sites 56 . These genes are unrelated at the primary sequence level, but predicted to link Rbpj to HDAC machinery, and include Smrt/Ncor2 , Spen/Mint/Sharp , Fhl1b//KyoT2 , Rita , Skip , L3mbtl3 and Kdm1a/Lsd1 57 59 . Interestingly, Kdm1a/Lsd1 is expressed in the retina from E17-P15, and its pharmacologic inhibition in retinal explants induced an upregulation of bHLH factor expression 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular S2 cleavage is due to the tumor necrosis factor-alpha converting enzyme (TACE), whereas S3 intramembrane cleavage is operated by a gamma secretase, which catalyzes the release of the intracellular domain of Notch (N-ICD) into the cytoplasm. N-ICD then translocates inside the nucleus and forms a complex with RBPjk/CSL (CBF1/Su(H)/Lag-1) [ 13 ]. RBPjk is a DNA-binding transcription factor, which acts in a large complex with other proteins.…”
Section: Diversity Of Notch Signaling Mechanismsmentioning
confidence: 99%
“…Notch signaling plays an important role in the tumor biology, including cell differentiation, proliferation, apoptosis, migration and invasion [ 7 10 ]. Increasing reports demonstrated that deregulation of Notch1 signaling can be observed in diverse tumor types, such as cervical cancer.…”
Section: Introductionmentioning
confidence: 99%